PERSEPSI GURU KEJURUAN SMK NEGERI 1 BUKITTINGGI TERHADAP PENERAPAN KOMPETENSI GURU ABAD 21 - 2128-2134, M. Yahya Almursyid (CIVED, 2018)
Abstract—This research is based on the problems at schools, this is based on interviews with  public relations and vocational teachers SMK Negeri 1 Bukittinggi is only 20% of teachers are able to use digital media for learning, and there are different perceptions of the application of digital media due to age factor so that not able to adapt to the development of digital media. This research is descriptive quantitative and the population is all vocational teachers of SMK Negeri 1 Bukittinggi which amounted to 101 people. To determine the sample of research using Simple Random Sampling method and obtained sample of 81 people. Data collection techniques in this study using a questionnaire with Likert Scale that has been tested its validity and obtained 4 invalid questionnaire results, reliability obtained results Cronbach's Alpha 0.949 are included in the category very high. Based on the results of data analysis with SPSS version 16.00 and Microsoft Excel 2007 obtained percentage value of each indicator that, the application of competence Digital Age Literacy categorized good with percentage 80,15%, application of competence Incentive Thinking categorized very good with percentage 81,58%, application of Effective Communication categorized good with percentage 80,91 %, and the application of High Productivity competency is categorized as good with percentage 65,29%. Key Words: Perception, Vocational Teacher, Teacher Competence 21st Century